ANATOMICAL ANALYSIS OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM AT GENERAL HIGHER EDUCATION IN INDONESIA - Muhammad Nasir; Syeh Hawib Hamzah; Muhammad Khairul Rijal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This article explores the anatomical characteristics of the Islamic Education Curriculum based on personal and community development in General Higher Education in Indonesia. This research is a qualitative study, words or actions of people observed and interviewed are the main data sources. The primary data sources of this study were elements of faculty leaders, heads of study programs, students, and lecturers of Islamic Religious Education. This study illustrates how the anatomical characteristics of Islamic Higher Education of General Islamic Education curriculum support strengthening personal and community development. The research findings show that the learning achievements of graduates, the content and teaching materials, the learning process or learning experience, and the assessment model illustrated in the curriculum structure, strongly support the development of responsibilities as individuals of Allah's servants and as Khalifah fi al-ardh. The aspect of personal development is the aspect of tathwir al-nafsi in the form of individual monotheism which includes the teaching of Islamic belief, strengthening of mahdhah and others. The aspect of tathwir al-ijetimaiy, illustrated in the strengthening of student social monotheism in the form of al-amr bi al-makruf wa al-nahy an al-mungkar, the human concept as caliph, democracy, science, technology, art, harmony, civil society, welfare, religious people, Islamic culture, Islamic political system, and democracy. The learning process is still dominated by increasing the understanding of the propositions, concepts, and theories with the teaching model of information processing. The internalization process through practice with social and humanistic teaching models still needs to be improved.